KESIAPAN BELAJAR SISWA TUNARUNGU YANG MENEMPUH PENDIDIKAN INKLUSI - Bagus Cakraningrat; Fuadah Fakhruddiana (HUMANITAS: Indonesian Psychological Journal, 2015)
AbstractThis research aims to know the deaf student readiness who took inclusive education to learn and to know the condition that supports and hampers it. This research used quantitative method by case approach. The data were collected by interview and documentation study. Content analysis was conducted to analyze the data.  According to the result of the research, it can be concluded that both of the subjects could be said ready for the exam at inclusive school. The supportive factors of the deaf students readiness are parents’ attention giving, cooperative teachers and friends’ help while the inhibiting factors that hamper their readinessare more to the technical problems such as lack of literacy ability that cause difficulties in understanding the lesson. Keywords : deaf, inclusive education, study readiness